Application Of Fuzzy Logic Controller For Tracting Global Maximum Power Of Partial Shade Pv System (Assosa University Whether Condition) - Assaye, Fetene (ASTU, 2020)
A solar photovoltaic (PV) system has been emerging out as one of the greatest potential renewable energy sources and is contributing significantly in the energy sector at present and at large in the future due to its nature of environmental friendly. The main challenge of the PV system is it depends upon the solar irradiation and any changes in the incoming solar irradiation will affect badly on the output of the PV system. Furthermore, solar PV power has large fluctuations due to partial shading condition. This implies, under partial shading conditions, multiple peaks are experienced in the power??voltage (P??V) characteristic curve of a photovoltaic (PV) array, and the conventional maximum power point tracking (MPPT) algorithms (or P&O MPPT algorithm) may fail to track the global maximum power point (GMPP. Furthermore, when the solar panel is directly connected to the load, the power that is delivered is not optimal. Therefore, this thesis proposes a maximum power point tracking (MPPT) in order to extract the GMPP from multiple peaks of the PV system for a potential maximum efficiency under partial shade conditions. In order to do so; first the PV system with resistive load is discussed, the modeling and the simulation of the PV module and the DC/DC converter (boost converter) are carried out using MATLAB software for different testing conditions. The objective of the proposed algorithm, FLC is to simultaneously solve inherent drawbacks in conventional MPPT algorithms. The performances of the conventional Perturb & Observe (P&O) algorithm and the proposed algorithm are compared by using MATLAB/Simulink 2015a, and the theoretical advantages of FLC were demonstrated. The results indicated that the proposed algorithm performed with faster tracking time, smaller output power oscillation, and higher efficiency, compared to that of the conventional P&O algorithm. This show that MPPT with FLC can give a big significant improvement on the performance of PV system under the conditions like varying irradiation and temperature, and partial shade. FLC technique gives better and more reliable control for this application.
Keywords: Pvs, Pv Cell, Pv Module, Pv Array, Matlab2015a Simulink, Mppt Gmp, Flc, P&O Algorithm, Pwm, Boost Converter, Ideal Switches